Avaliação de risco dietético: uma revisão sistemática e determinação de agrotóxicos em arroz integral, parboilizado e polido produzidos no Brasil - Skonieski, Calinca (2024)
This study aimed to evaluate the presence of residues from 155 pesticides in 216 samples of polished, parboiled, and brown rice commercialized between 2019 and 2024. To achieve this, a multiresidue method was validated prior to sample analy-sis, following the guidelines of the SANTE 11312/2021 document. Rice samples were collected from three cities/regions in Rio Grande do Sul (Santa Maria/Central-West, Pelotas/Southeast, and Uruguaiana/Southwest), the state's main rice-pro-ducing regions. The pesticide residue monitoring results were used to assess the potential chronic dietary exposure risk to consumers. Of the 155 pesticides ana-lyzed, 20 were detected, with brown rice showing the highest frequency of resi-dues, followed by parboiled and polished rice. However, none of the detected pes-ticides exceeded the maximum residue limits established by Brazilian regulations, although some exceeded the limits defined by European regulations. Additionally, three pesticides that are not approved for use in rice cultivation were detected, and two of them are banned in Brazil. Furthermore, 96.8% of the 216 samples tested positive for one or more pesticides. Despite the high contamination levels, chronic risk assessment confirmed that the rice samples are safe for human consumption, indicating no health risks. These findings underscore the necessity of continuous pesticide residue monitoring in rice and the importance of developing effective reg-ulations to ensure the provision of safe food to consumers.